The Depiction of American Pastoral according to Philip Roth - Bucháčková, Lucie (Univerzita Pardubice, 2023)
The bachelor thesis analyzes Philip Roth's novel American Pastoral and his portrayal of the American dream. It focuses on the reflection of the societal, political, and cultural events and phenomena of the 1960s in the United States and their impact on the American everyman depicted in Roth's book.
Americká idyla podle Philipa Rotha
Keywords: Americká idyla; Roth, Philip; americký sen; 60. léta 20. století; American Pastoral; Roth, Philip; American dream; the 1960s